Multimodal mimicry of hosts in a radiation of parasitic finches. (1st November 2020) - Jamie, Gabriel A.; Van Belleghem, Steven M.; Hogan, Benedict G.; Hamama, Silky; Moya, Collins; Troscianko, Jolyon; Stoddard, Mary Caswell; Kilner, Rebecca M.; Spottiswoode, Claire N.
Abstract: Brood parasites use the parental care of others to raise their young and sometimes employ mimicry to dupe their hosts. The brood‐parasitic finches of the genus Vidua are a textbook example of the role of imprinting in sympatric speciation. Sympatric speciation is thought to occur in Vidua because their mating traits and host preferences are strongly influenced by their early host environment. However, this alone may not be sufficient to isolate parasite lineages, and divergent ecological adaptations may also be required to prevent hybridization collapsing incipient species. Using pattern recognition software and classification models, we provide quantitative evidence that Vidua exhibit specialist mimicry of their grassfinch hosts, matching the patterns, colors and sounds of their respective host's nestlings. We also provide qualitative evidence of mimicry in postural components of Vidua begging. Quantitative comparisons reveal small discrepancies between parasite and host phenotypes, with parasites sometimes exaggerating their host's traits. Our results support the hypothesis that behavioral imprinting on hosts has not only enabled the origin of new Vidua species, but also set the stage for the evolution of host‐specific, ecological adaptations.